2018
DOI: 10.3389/fmicb.2018.01695
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polymorphisms in the SjSP-13 Gene of Schistosoma japonicum on Its Diagnostic Efficacy and Immunogenicity

Abstract: Schistosomiasis japonica is one of the most prevalent parasitic diseases in China. The scarcity of effective diagnostic tools is a major factor that contributes to the high prevalence of schistosomiasis japonica. SjSP-13 is a promising serological diagnostic biomarker of the disease. However, it is unclear whether polymorphisms in SjSP-13 affect its diagnostic efficacy and immunogenicity. Here, we found the SjSP-13 gene was highly polymorphic, and all the alleles of the gene were clustered into two clades, cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…In addition, the polymorphism of SjSP-13 gene may be the other factor explaining the reduction of sensitivity of peptide-ELISA. The peptide sequence of the two epitopes identified in the present study was highly polymorphic according to our previous study [22].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In addition, the polymorphism of SjSP-13 gene may be the other factor explaining the reduction of sensitivity of peptide-ELISA. The peptide sequence of the two epitopes identified in the present study was highly polymorphic according to our previous study [22].…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have identified a highly immunogenic antigen, SjSP-13, a member of a multigene family of saposin-like proteins. This antigen could be widely recognized by serum IgG of infected humans and has been applied for immunodiagnosis of schistosomiasis [14, 22]. Due to their highly immunogenic properties, B-cell epitopes of SjSP-13 were identified in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al 20 discovered the Schistosoma japonicum secreted protein 13 (SjSP-13) gene as a diagnostic tool for detecting schistosome infections. All the alleles of the gene were clustered into two clades (Clade A and B).…”
Section: Diagnosismentioning
confidence: 99%
“…Furthermore, the immunogenicity of Clade A was higher. Xu et al 20 stated that it was not necessary to combine Clade A and B for diagnostics of schistosomiasis.…”
Section: Diagnosismentioning
confidence: 99%